Analysis of Grit and Passion Levels for Physical Activity in the Oerang TjianzoeRun Running Community: A Case Study of a Non-Professional Running Community in Indonesia - Ismail Hasani; Taupik Rochman; Muhamad Syamsul Taufik (Physical Activity Journal (PAJU), 2026)
The purpose of this study was to identify the level of grit and interest in sports and fitness among members of the Oerang TjianzoeRun Running Community in Cianjur Regency. It is believed that psychological components such as grit, which include consistency of interest and persistence, as well as passion, both harmonious and obsessive, are crucial for maintaining sustainable physical activity. This study used a quantitative descriptive approach with a purposively selected sample of 40 active participants. The Grit-S and Passion Scale questionnaires were distributed and administered through Google Forms. The results showed that most participants had moderate levels of grit (57.5%), moderate passion (60%), and moderate physical fitness (55%). The results suggest that, despite the strong desire to exercise, increased motivation and persistence, as well as external support, such as a positive social and community environment, are needed. It is recommended that the community organize motivational mentoring programs, provide a variety of challenging exercises, and social activities that strengthen a sense of community to continuously improve grit, passion, and physical fitness.